Conjunctival melanoma copy number alterations and correlation with mutation status, tumor features, and clinical outcome. (19th February 2019) - Kenawy, Nihal; Kalirai, Helen; Sacco, Joseph J.; Lake, Sarah L.; Heegaard, Steffen; Larsen, Ann‐Cathrine; Finger, Paul T.; Milman, Tatyana; Chin, Kimberly; Mosci, Carlo; Lanza, Francesco; Moulin, Alexandre; et al.
Abstract: Relatively little is known about the genetic aberrations of conjunctival melanomas (CoM) and their correlation with clinical and histomorphological features as well as prognosis. The aim of this large collaborative multicenter study was to determine potential key biomarkers for metastatic risk and any druggable targets for high metastatic risk CoM. Using Affymetrix single nucleotide polymorphism genotyping arrays on 59 CoM, we detected frequent amplifications on chromosome (chr) 6p and deletions on 7q, and characterized mutation‐specific copy number alterations. Deletions on chr 10q11.21‐26.2, a region harboring the tumor suppressor genes, PDCD4, SUFU, NEURL1, PTEN, RASSF4, DMBT1, and C10orf90 and C10orf99, significantly correlated with metastasis (Fisher's exact, p  ≤ 0.04), lymphatic invasion (Fisher's exact, p  ≤ 0.02), increasing tumor thickness (Mann–Whitney, p  ≤ 0.02), and BRAF mutation (Fisher's exact, p  ≤ 0.05). This enhanced insight into CoM biology is a step toward identifying patients at risk of metastasis and potential therapeutic targets for systemic disease.